Professional activity of stomatherapists graduated from the Federal University of Minas Gerais (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objectives: This study aimed to identify the area of professional activity, characterize the trajectory and clinical practice in the area of stomatherapy, and identify further training as a specialist. Method: A descriptive study with a quantitative approach was conducted by applying an online questionnaire to graduates of the specialization course in Stomatherapy of the Federal University of Minas Gerais, which began in 2007, totaling 97 by 2015. The convenience sample was composed of 84 specialists who agreed to answer the questionnaire considering the study variables. Results: Most of the graduates were female (86%), aged between 31 and 40 years (68%), residents (58%) and working (59.6%) in Belo Horizonte. They remain active in their specialty area (70%), with predominance of stoma and wound care (31%), in care activities (29.3%), in the hospital area (27.3%) and in the health public sector (38%). The pursuit of specialization was predominantly motivated by interest in technical-scientific development (48.5%) and (69%) of the graduates continues capacitating after specialization. Conclusion: Stomatherapy is expanding in the national market, requiring the continuation of national research for a broader view of the specialty.